2017
DOI: 10.1523/jneurosci.0851-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-3p Is a Key Regulator of IL-1β-Dependent Synaptopathy in Neuroinflammation

Abstract: MicroRNAs (miRNA) play an important role in post-transcriptional gene regulation of several physiological and pathological processes. In multiple sclerosis (MS), a chronic inflammatory and degenerative disease of the CNS, and in its mouse model, the experimental autoimmune encephalomyelitis (EAE), miRNA dysregulation has been mainly related to immune system dysfunction and white matter (WM) pathology. However, little is known about their role in gray matter pathology. Here, we explored miRNA involvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Chronic-progressive EAE was induced as previously described ( 7 ). Briefly, six-eight weeks old C57BL/6 (Charles River, Milan, Italy) female mice were active immunized with an emulsion containing 200 μg/animal of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG35–55, 85% purity; Espikem, Prato, Italy) in Complete Freund’s Adjuvant (CFA; Difco, Los Altos, CA, USA) containing 8mg/ml lyophilized Mycobacterium tuberculosis (BD, M. Tubercolosis Des.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic-progressive EAE was induced as previously described ( 7 ). Briefly, six-eight weeks old C57BL/6 (Charles River, Milan, Italy) female mice were active immunized with an emulsion containing 200 μg/animal of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG35–55, 85% purity; Espikem, Prato, Italy) in Complete Freund’s Adjuvant (CFA; Difco, Los Altos, CA, USA) containing 8mg/ml lyophilized Mycobacterium tuberculosis (BD, M. Tubercolosis Des.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Lei et al (3) demonstrated that miR-142-3p influenced the proliferation of non-small cell lung cancer cells through repression of TGFβR1. miR-142-3p have been highlighted as a key molecular player in IL-1β-mediated synaptic dysfunction, which indicated its neuroprotective role in multiple sclerosis (4). …”
Section: Introductionmentioning
confidence: 99%